Evaluation of Malaysian oil palm progenies for susceptibility, resistance or tolerance to Fusarium oxysporum f. sp. elaeidis and defence‐related gene expression in roots. (12th October 2014) - Rusli, M. H.; Idris, A. S.; Cooper, R. M.
<x xml:space="preserve">Abstract</x> Vascular wilt of oil palm caused by Fusarium oxysporum f. sp. elaeidis (Foe) is a devastating disease in West and Central Africa. As the oil palm industry in southeast Asia is still expanding, so is the oil palm germplasm collection through the importation of seed and pollen from Africa, the centre of diversity for Elaeis guineensis. There is a risk of inadvertent spread of the disease on contaminated seed or pollen. Regular re‐evaluation of the reaction of currently grown palm genotypes towards Foe is clearly required for biosecurity. This study has demonstrated that four Malaysian oil palm progenies, three in current or recent commercial use, are highly susceptible to infection by at least one of two African isolates of Foe, representing different countries, aggressiveness and vegetative compatibility groups. Symptoms and reduction of palm growth generally reflected the extent and intensity of systemic colonization by Foe. Progeny PK 5463 expressed partial resistance to Foe isolate F3, but not to isolate 16F, displaying significantly milder symptoms and supporting less widespread vascular colonization. This relatively incompatible interaction was used to study expression of potential defence‐related genes during root infection when compared to a susceptible palm–isolate combination. The only significant response was an early up‐regulation of chitinase in resistant palms. The research revealed at least one progeny–isolate differential interaction, and the associated resistance expression suggests a component of tolerance, because colonization by Foe was systemic in both compatible and incompatible combinations.